2005
DOI: 10.1161/circulationaha.105.547331
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Atrial Mechanical Remodeling and Its Consequences

Abstract: T he principal function of the left atrium is to modulate left ventricular (LV) filling and cardiovascular performance through reservoir, conduit, and booster pump functions; the latter is often (mistakenly) regarded synonymously with atrial function, and in contrast to the reservoir and conduit phases, has been studied extensively. Typically, the importance of atrial contraction has been estimated by measurements of cardiac output and end-diastolic volumes both with and without effective atrial systole, by re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 24 publications
2
31
0
2
Order By: Relevance
“…These studies support the hypothesis that atrial functional remodelling and reduced atrial contraction can result in subsequent thromboembolism (8). Therefore, LA strain analysis may provide an invaluable prognostic tool for AF; albeit larger prospective studies in stroke patients are required to confirm these early reports.…”
Section: La Strain and Strokesupporting
confidence: 66%
See 1 more Smart Citation
“…These studies support the hypothesis that atrial functional remodelling and reduced atrial contraction can result in subsequent thromboembolism (8). Therefore, LA strain analysis may provide an invaluable prognostic tool for AF; albeit larger prospective studies in stroke patients are required to confirm these early reports.…”
Section: La Strain and Strokesupporting
confidence: 66%
“…While previously left atrial (LA) size was utilised, the role of LA function as a biomarker is increasingly being evaluated (4), both independently and also in combination with LA size (5-7). However, LA function is complex, comprising of three main components: reservoir function in systole when blood fills the left atrium, as a conduit in early diastole corresponding to passive left ventricular filling and as an active contractile chamber in late diastole (8,9).…”
mentioning
confidence: 99%
“…According to Frank-Starling curve, to a certain extent, LA compensatory contractility and LA ejection force (% LAVIact) are increased at late diastole, which can maintain the normal cardiac output [16][17][18][19][20][21][22] . Muranaka et al [23,24] reported that the LA reserve and channel function of patients with DM were decreased. The possible reason for the diversity was attributed to the follows : (1) The heart change of this group was at the early stage; (2) There was no significant difference in %iLAVIe.…”
Section: Discussionmentioning
confidence: 99%
“…After cardioversion, peak atrial strain rate during late diastole is a descriptor of atrial function [23]. However the reservoir function of the LA is governed by atrial compliance, which may play an important role in modulating systolic and diastolic function of the LA [24,25]. LA strain and strain rate during ventricular systole reflect atrial distensibility [24] and can be used as an index of LA reservoir function [26].…”
Section: Reservoir Function For New Onset Afmentioning
confidence: 99%